Autophagy regulates apoptosis on the level of the death‐inducing signalling complex. (3rd July 2017) - Nowikovsky, Karin; Bergmann, Michael
Abstract : The interactions between apoptotic and autophagic proteins via the proteolytic systems are known mechanisms through which autophagy and apoptosis regulate each other. In this issue of The FEBS Journal, Gentle and colleagues propose a mechanism through which autophagy regulates the induction of apoptosis at the level of the TIR‐domain‐containing adaptor‐inducing interferon‐β (TRIF) in TLR signaling.